Note that there is no requirement that the αi , αi be integers.

1

If these conditions are satisﬁed then (α) majorises (α ), which we write as (α) For example: • (0, 3, 0) • (4, 0, 0, 0) • (5, 0, −1) • (2, 1, 1, 1) • (4, 1, 1, 1) (1, 0, 2) (2, 0, 2) since the number of elements is diﬀerent (2, 2, 0) since terms cannot be negative (1, 1, 1, 1) since 2 + 1 + 1 + 1 = 1 + 1 + 1 + 1 (3, 3, 1, 0) since 4 + 1 3+3 (α )

Symmetric Means Suppose we have n positive reals, xi and a sequence (α). Then we can construct a function F (x1 , x2 , . . . , xn ) = xα1 xα2 . . . xαn 1 2 n We can, of course, permute the xi to give, for example, F (x2 , x1 , . . . , xn ) = xα1 xα2 . . . xαn 2 1 n We denote the sum over all n! permutations of the xi by !F (x1 , x2 , . . . , xn ) Finally, we deﬁne the symmetric mean as [α] = 1 n! !F (x1 , x2 , . . . , xn )

Obviously, [α] is a function of x1 , x2 , . . . , xn . If we swap any of the xi , [α] is unchanged. That is why it is called a symmetric mean! For example: • If (α) = (0, 3, 1) then F (x1 , x2 , x3 ) = x3 x3 2 • If (α) = (2, 1) then !F (x, y) = x2 y + y 2 x 2

• If (α) = (1, 3, 2) then the symmetric mean [α] = 1 (x1 x3 x2 + x1 x3 x2 + x2 x3 x2 + x2 x3 x2 + x3 x3 x2 + x3 x3 x2 ) 2 3 3 2 1 3 3 1 1 2 2 1 3!

Muirhead’s Inequality Now that we have deﬁned majorisation and symmetric means, the statement of Muirhead’s inequality is easy: Muirhead’s Theorem: If (α) (α ) then [α] ≥ [α ]. There is equality if and only if (α) and (α ) are identical or all the xi are equal. For example: • For positive x, y, prove that 2(x5 + y 5 ) ≥ (x2 + y 2 )(x3 + y 3 ). Solution: We have: (5, 0) (3, 2)

therefore by Muirhead’s inequality: 1 3 2 1 5 (x + y 5 ) ≥ (x y + x2 y 3 ) 2! 2! so x5 + y 5 ≥ x3 y 2 + x2 y 3 hence 2(x5 + y 5 ) ≥ x5 + x3 y 2 + x2 y 3 + y 5 = (x2 + y 2 )(x3 + y 3 ) • BMO1 2002 Round 1 Q3: For positive real x, y, z such that x2 + y 2 + z 2 = 1 prove that x2 yz + xy 2 z + xyz 2 ≤ Solution: We have (4, 0, 0) and (2, 2, 0) 3 (2, 1, 1) (2, 1, 1) 1 3

therefore 2 4 2 2 (x + y 4 + z 4 ) ≥ (x yz + xy 2 z + xyz 2 ) 3! 3! and 2 2 2 2 2 (x y + y 2 z 2 + z 2 x2 ) ≥ (x yz + xy 2 z + xyz 2 ) 3! 3! i.e. x4 + y 4 + z 4 ≥ x2 yz + xy 2 z + xyz 2 and x2 y 2 + y 2 z 2 + z 2 x2 ≥ x2 yz + xy 2 z + xyz 2 Adding the ﬁrst to twice the second gives: (x4 + y 4 + z 4 ) + 2(x2 y 2 + y 2 z 2 + z 2 x2 ) ≥ 3(x2 yz + xy 2 z + xyz 2 ) Rearranging: (x2 + y 2 + z 2 )2 ≥ 3(x2 yz + xy 2 z + xyz 2 ) But x2 + y 2 + z 2 = 1, so 1 ≥ 3(x2 yz + xy 2 z + xyz 2 ) 1 x2 yz + xy 2 z + xyz 2 ≤ 3 Exercises • BMO1 1996 Round 1 Q5: Let a, b and c be positive real numbers. Prove that 4(a3 + b3 ) ≥ (a + b)3 and 9(a3 + b3 + c3 ) ≥ (a + b + c)3 • For non-negative real x, y, z, prove that the RMS Mean is greater than or equal to the Arithmetic Mean, which in turn is greater than or equal to the Geometric Mean, which in turn is greater than or equal to the Harmonic Mean. I.e.: a2 + b 2 + c 2 a+b+c 3 ≥ ≥ (xyz)1/3 ≥ 3 3 1/x + 1/y + 1/z

4